Analgesia in therapeutic dentistry: methodological and topographical aspects of the workshop. - Dmitrieva, E. A. (Морфологія / Morphologia / Morfologìâ, 2015)
The article presents the main methodological aspects of practical training at the training on «Analgesia in therapeutic dentistry». Attention is focused on the matters of classification methods and types of anesthesia of pathological processes of maxillofacial region and their advantages and disadvantages, indications and contraindications for anesthesia for therapeutic interventions on questions of select the most effective anesthetic injection systems and technology of injection itself.